Cash Flow Analysis on Telkom Indonesia’s 2022 Financial Statement - Syachbrani, Warka (Phinisi Applied Accounting Journal, 2023)
This research discusses cash flow analysis at PT Telkom Indonesia (Persero) Tbk. Cash flow analysis is the process of examining/evaluating the cash inflow and outflow of an entity to determine the financial health of a company over a certain period of time. Research on cash flow analysis at PT Telkom Indonesia is interesting to study because it provides a direct picture of the company's financial condition at that time. PT Telkom Indonesia. Research on this topic is conducted with the aim of providing important insights into a company's financial health and operational performance, as well as assisting in short-term and long-term financial planning. The research method used is a quantitative method which involves the use of numbers and quantitative data to measure, compare and evaluate company cash flows. Keywords: Cash flow, financial performance, cash flow ratio